MNGI-07. TRIMETHYLATED H3K27 AND EZH2 EXPRESSION IN MENINGIOMA: CORRELATION WITH TENDENCY TO RECUR. (11th November 2019) - Calatozzolo, Chiara; Patanè, Monica; Farinotti, Mariangela; DiMeco, Francesco; Finocchiaro, Gaetano; Pollo, Bianca
Abstract: Meningiomas are the most frequent primary CNS tumors, usually benign (WHO grade I), but in the 25–30% more aggressive tumors (grade II-III). Histopathological criteria (WHO 2016) are unsatisfactory to recognize meningiomas with tendency to recur. Recent studies have identified some mutations associated with histological features and location (i.e. BAP1 mutation in rhabdoid subtype), while risk stratification schemes based on DNA methylation subgroups have been proposed. Epigenetic modifications of histones play a pivotal role in tumorigenesis, the methylation of lysine 27 (K27) of histone H3 controlled by EZH2 subunit of PRC2 complex. BAP1 could be also involved in epigenetic regulation of PRC2 complex. The deregulation of H3K27 methylation has been found associated with recurrence risk in grade II meningiomas. Aim of the present study was to evaluate histone H3 methylation profile in a group of meningiomas of different grade with follow-up longer than 10 years, comparing non-recurrent to recurrent ones. We performed an immunohistochemical study on 145 meningiomas (50 grade I, 80 grade II and 15 grade III), investigating the expression of trimethylated H3K27 (H3K27me3), EZH2 and BAP1. The results were related to clinical data obtained from our Institutional Tumor Registry and evaluation of clinical reports. We observed a loss of H3K27me3 expression only in grade II and III meningiomas in 18% of cases, without correlation with tendency to recur. EZH2 showed increased percentage of positive nuclei related to the grade. In the group of grade I meningioma EZH2 expression was associated to recurrences. We didn't observe loss of BAP1 expression. In conclusion, our data suggest that immunohistochemical evaluation of H3K27me3 and EZH2 could be a useful tool to better stratify meningioma with high risk of recurrence. Moreover, EZH2 could be of interest as therapeutic target. Molecular investigations in a larger cohort are needed to confirm these results.